Caracterização limnológica e de sedimentos da Lagoa dos Barros, Osório, Sul do Brasil - Agostini, Andrigo Ulian (My University, 2019)
Large shallow lakes are rare but relevant to ecosystems and humans. These systems have specific ecological characteristics related to its morphology, water and sediment characteristics. The comprehension of the processes of a lake is enhanced by analyzing its past conditions. The aim of this study was to characterize the present and past ecology conditions of Lagoa dos Barros, a lake in southern Brazilian coast. The study of present conditions combined bathymetric surveys, morphometric analyses, and assessments of water and biological communities. For the past, the analysis included evaluation of physical, chemical and biological (diatoms) components in a 35 cm sediment profile. Lagoa dos Barros shows peculiar characteristics related to its high mineral turbidity and limitation of the system productivity due to the low light availability in the water column, even with nutrients available. The base for this condition is the association between a flat and shallow morphology, the small size of sediment and the high incidence of wind in the region. In the recent past, the lake undergoned variations in turbidity and salinity conditions, evidencing its susceptibility to changes in the drainage basin associated with water level oscillations. The singularity of the lake demands an improved management of its uses.
Lagos rasos de grandes dimensões são raros, porém relevantes aos ecossistemas e ao homem. Estes sistemas apresentam características ecológicas específicas, de acordo com as características da morfologia, água e do sedimento. A compreensão dos processos de um lago é ampliada pela análise de suas condições passadas. O objetivo deste estudo foi caracterizar as condições ecológicas no presente e passado da Lagoa dos Barros, um lago na região costeira sul brasileira. As condições no presente foram estudadas aliando levantamentos batimétricos, análises morfométricas, e avaliações de características da água e de comunidades biológicas. Para o passado, foi realizada a determinação de componentes físicos, químicos e biológicos (diatomáceas) em um perfil de 35 cm de sedimento. A singularidade da Lagoa dos Barros é derivada da alta turbidez mineral e limitação da produtividade do sistema pela baixa disponibilidade de luz na água, mesmo na presença de nutrientes. Essa condição é fundamentada na associação entre a morfologia plana e rasa, pequena dimensão granulométrica dos sedimentos e a alta incidência de vento na região. O lago passou, no passado recente, por variações nas condições de turbidez e salinidade, evidenciando sua susceptibilidade a alterações na bacia de drenagem associadas às mudanças climáticas. A singularidade do lago requer uma gestão melhorada de seus usos.
Keywords: Lagos; Água doce; Limnologia; Barros, Lagoa dos; Lakes; Fresh water; Limnology